“THE MAD PACT” AS A STORY OF ONE INITIATION: VITALY BENDER’S SHORT STORY “THE SECRET” IN THE CONTEXT OF THE MODERNIST SEARCH OF THE AUTHOR - Бузов, Антон (Літературний процес: методологія, імена, тенденції, 2018)
The article presents a vision of Vitaly Bender’s text as an attempt at self-identification of a Ukrainian emigrant in the discourses and post-war European exile. Particular attention is focused on the reproduction of the existential initiations of representatives of Ukrainian emigration in a foreign mental space. It is noted that the emigration dimension of the life of Ukrainians in the middle and second half of the 20th century is determined by the presence of such ideological dominants as the desire to rediscover lost identity under exile conditions. It is emphasized that to achieve this goal, the heroes of Vitaly Bender’s works not only resort to confrontation with assimilative tendencies, but also strive to return to the European mental and cultural context without losing their own self. The life of the emigrant in the writer’s artistic vision appears as a continuous existential initiation in the new space, thus it can be argued that the work of Vitaly Bender is an organic component of the general artistic and philosophical discourse of the Ukrainian writer diaspora of the postwar period. It is a question of the traditional model of the fable organization of a literary work. The initial phase in this system is the phase of isolation. At this stage, the spatial and temporal characteristics of the work, its key actors, are singled out. The second phase — the phase of partnership — is manifested in the novel at different stages in the development of its plot. It is realized through the establishment of new intersubject connections, in particular, the acquisition by the hero of “helpers” or “wreckers”. The transition to the liminal stage symbolizes the beginning of a direct confrontation with death. The phase of transformation is a complex of spiritual changes of the main characters after the death test.The article considers the vertical dominants of Vitaly Bender’s novel “The Secret” as exemplary in relation to the modernist searches of the author of the work. The analysis of the story at the plot level. In the work, the phases of isolation, establishment of partnership, and death testing are sequentially highlighted. The use of classical plot schemes in the study of the literary heritage of Vitaly Bender makes it possible to more fully reveal not only the universal pathos and humanistic focus of the novel text, but also its ideological and aesthetic originality. It is noted that in the specified work the author reveals a special dimension of the initiation of a Ukrainian emigrant in a foreign land - an intimate measurement. It was emphasized that the identity lost in the conditions of emigration is regained through the formation of personal relations of the main characters of the analyzed work. It is concluded that the appeal of Vitaly Bender to this issue is an indicator of his modernist interests.